2021
DOI: 10.1186/s12880-021-00600-9
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of use, effectiveness and safety of gadolinium contrast agents: a European prospective cross-sectional multicentre observational study

Abstract: Background The EU gadolinium-based contrast agents (GBCA) market has changed in recent years due to the European Medicines Agency decision to suspend the marketing authorisation of linear GBCA and the marketing authorisation of new generic macrocyclic GBCA. The study aims to understand the patterns of (GBCA) use, and to study the effectiveness and safety of GBCA in routine practice across Europe. Methods Prospective, cross-sectional, multicentre, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…Consistent with the results of the present study, a 2015 review of previous studies that evaluated the safety and efficacy of gadoteric acid also showed a high level of improvement in diagnosis upon the use of gadoteric acid, with good or excellent image quality reported in 95 to 100% of cases [ 13 ]. Similar findings were reported recently in a prospective, cross-sectional, multicenter, observational study, confirming that GBCAs are used appropriately in Europe for a wide range of indications [ 14 ]. The study demonstrated a significant increase in diagnostic confidence after GBCA use and confirmed the good safety profile of GBCAs, with comparable results for all agents used (Clariscan, Dotarem (gadoteric acid), Gadovist (gadobutrol), and ProHance (gadoteridol)) [ 14 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with the results of the present study, a 2015 review of previous studies that evaluated the safety and efficacy of gadoteric acid also showed a high level of improvement in diagnosis upon the use of gadoteric acid, with good or excellent image quality reported in 95 to 100% of cases [ 13 ]. Similar findings were reported recently in a prospective, cross-sectional, multicenter, observational study, confirming that GBCAs are used appropriately in Europe for a wide range of indications [ 14 ]. The study demonstrated a significant increase in diagnostic confidence after GBCA use and confirmed the good safety profile of GBCAs, with comparable results for all agents used (Clariscan, Dotarem (gadoteric acid), Gadovist (gadobutrol), and ProHance (gadoteridol)) [ 14 ].…”
Section: Discussionsupporting
confidence: 90%
“…Similar findings were reported recently in a prospective, cross-sectional, multicenter, observational study, confirming that GBCAs are used appropriately in Europe for a wide range of indications [ 14 ]. The study demonstrated a significant increase in diagnostic confidence after GBCA use and confirmed the good safety profile of GBCAs, with comparable results for all agents used (Clariscan, Dotarem (gadoteric acid), Gadovist (gadobutrol), and ProHance (gadoteridol)) [ 14 ].…”
Section: Discussionsupporting
confidence: 90%
“…The present study is a subanalysis of the data from the above European study, to assess the real-world safety and efficacy of GBCAs, including Clariscan for CNS (brain and spine) examinations at recommended/on label doses in the USA. [10]…”
Section: Methodsmentioning
confidence: 99%
“…The data for this study has been obtained from a larger scale European study, a cross-sectional multicenter observational study with prospective recruitment performed in patients scheduled for gadolinium contrast-enhanced magnetic resonance imaging (CE-MRI) as part of their routine clinical workup. [10] The study was registered on https://clinicaltrials.gov with identifier NCT01523873.…”
Section: Methodsmentioning
confidence: 99%
“…1 Gadolinium-based contrast agents (GBCAs) are widely used for contrast-enhanced magnetic resonance imaging in over 450 million patients worldwide. 1 Gadolinium-based contrast agents are classified into extracellular fluid (ECF), hepatobiliary, and blood-pool agents by their biodistribution profile. 2,3 Popular GBCAs (eg, gadobutrol…”
mentioning
confidence: 99%